Aluminum-silicon alloy, preparation method and application thereof and aluminum-silicon alloy product

By adding specific components and composite grain refiners to aluminum-silicon alloys to form a core-shell structure, the problem of poor grain refinement in existing technologies is solved, achieving efficient grain refinement and performance improvement.

CN119410972APending Publication Date: 2025-02-11UNIV OF SCI & TECH BEIJING +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541297.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing grain refiners for aluminum-silicon alloys show a significant decrease in refining effect when the Si content is greater than 5%, failing to meet the refining requirements of sub-aluminum-silicon alloys and affecting the strength and plasticity of the alloy.

Method used

A specific aluminum-silicon alloy formulation, including Si, Mg, Mn, Fe, Nb, B, Sr and TiCN, is used. By adding Nb-B and TiCN particles, a core-shell structure is formed to restrict grain growth. The refinement effect of the alloy is improved by ultrasonic treatment and aging heat treatment.

Benefits of technology

It significantly improves the refining efficiency of aluminum-silicon alloys, enhances the alloy's strength, plasticity, and castability, extends mold life, and improves the overall performance of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410972A_ABST
    Figure CN119410972A_ABST
Patent Text Reader

Abstract

The invention relates to an aluminum-silicon alloy, a preparation method and application thereof, and an aluminum-silicon alloy product, the aluminum-silicon alloy comprises the following components by mass: 8.5%-10% of S ; 0.1% to 0.5% of Mg; 0.35% to 0.65% of Mn; 0.1% to 0.2% of Fe; 0.05% to 0.2% of Nb; 0.01% to 0.04% of B; 0.01%-0.02% of Sr, and 0.5%-1% of Ti CN; the total content of other impurities is less than or equal to 0.5%. The aluminum-silicon alloy is good in refining effect and has good tensile strength and yield strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum-silicon alloy and a preparation method and application thereof, and an aluminum-silicon alloy product. Background Art

[0002] Lightweighting of automobiles has become a current development trend. Aluminum-silicon alloys have replaced steel as the mainstream material for automobile structural parts due to their high strength, corrosion resistance, good castability and formability. Among them, grain refinement can not only improve the strength of aluminum-silicon alloys, but also improve the plasticity of the alloy by refining and dispersing the eutectic Si phase and lamellar iron-rich phase. However, the existing cast aluminum-silicon alloys generally achieve grain refinement by adding Al-T iB refiners, but when the Al-T iB refiner has a Si content greater than 5%, the refinement effect will be significantly reduced, and the refiner cannot meet the refinement requirements of sub-aluminum-silicon alloys. Summary of the invention

[0003] The purpose of the present invention is to provide an aluminum-silicon alloy and a preparation method and application thereof, and an aluminum-silicon alloy product, so as to achieve a better refinement effect of the aluminum-silicon alloy.

[0004] To achieve the purpose of the present invention, the technical solution adopted is:

[0005] An aluminum silicon alloy comprises the following components, measured by mass percentage: 8.5% to 10% Si; 0.1% to 0.5% Mg; 0.35% to 0.65% Mn; 0.1% to 0.2% Fe; 0.05% to 0.2% Nb; 0.01% to 0.04% B; 0.01% to 0.02% Sr, 0.5% to 1% TiCN; the total content of other impurities is ≤0.5%, and the balance is Al.

[0006] In some of the embodiments, the mass ratio of Mn to Fe is (1.5-3.2):1, and the mass ratio of Nb to B is (5-9):1.

[0007] In some of the embodiments, Nb and B are added in the form of Al-Nb-B master alloy.

[0008] In some of the embodiments, the TiCN is a ceramic particle with a size of 20 to 200 nanometers.

[0009] The present invention also provides a method for preparing the aluminum-silicon alloy, comprising the following steps:

[0010] S1. Batching and smelting: Si, Mn and Al are batched according to mass percentage and put into a smelting furnace. The temperature of the smelting furnace is raised to 790°C-810°C until all the above alloys are melted. The temperature of the smelting furnace is lowered to 775°C-785°C, Nb and B are added to the melt, and stirred for 30s-40s after Nb and B are completely melted. The temperature of the smelting furnace is further lowered to 730°C-735°C before adding Mg and Sr.

[0011] S2. Refining and pouring: After degassing and refining for 30min to 35min, remove the slag; after removing the slag, add TiCN into the melt and stir for 3min to 5min, and then ultrasonically treat for 3min to 5min; after refining, let it stand for 15min to 20min, and then pour it, and the pouring temperature is 730℃ to 740℃.

[0012] In some of the embodiments, in step S1, the selected elements are added in the form of: Al-Si master alloy, Al-Mn master alloy, Al-Sr master alloy, industrial pure aluminum with a purity of 99.9%, Al-Nb-B master alloy, and industrial pure magnesium with a purity of 99.9%.

[0013] In some of the embodiments, in step S2, after adding TiCN into the melt, stirring is performed for 3 minutes using a graphite rod.

[0014] In some embodiments, in step S2, the ultrasonic vibration frequency is 19KHz to 21KHz, and during operation, the ultrasonic probe is inserted below the liquid surface, and the probe is 10mm to 15mm away from the liquid surface.

[0015] The present invention also provides an application of the aluminum-silicon alloy in automobile structural parts.

[0016] The present invention also provides an aluminum-silicon alloy product as mentioned above, comprising the aluminum-silicon alloy as mentioned above.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] In the aluminum-silicon alloy of the present invention, Si element is an alloy basic element, and the addition of Si can reduce volume shrinkage and improve fluidity, thereby improving the castability of the aluminum alloy; at the same time, the addition of Si will lead to the formation of large-layer lamellar eutectic Si, and the large-plate lamellar eutectic Si structure can be transformed into fine fibers through a trace amount of Sr modification treatment to improve the plasticity of the alloy; Mg element and Si element can form Mg2Si phase, and after aging heat treatment, a dispersion strengthening phase can be precipitated in the alloy to improve the strength of the alloy; Mn element can transform the lamellar β-Fe phase in the alloy into a rounded Chinese character-shaped α-Fe phase, thereby improving the ductility of the alloy, and at the same time, the addition of Mn element will reduce the solubility of Fe element in Al, improve demoulding property, thereby extending the life of the mold; the role of Nb element and B element is to improve the nucleation efficiency of the substrate by forming nucleation substrates NbB2 and AlNB3 that are resistant to "Si" poisoning; the role of TiCN is to densely adhere to the periphery of the grains, greatly restricting the rapid growth of the grains, and Nb-B and TiCN have a great influence on the growth of the grains. The composite addition of CN eventually forms a spatial distribution of Nb-BT i CN particles with a "core-shell" structure in the core and boundary of the grains, while having the advantages of micron-scale particles providing nucleation substrate and nano-scale particles restricting growth, and has a higher refinement efficiency than conventional refiners. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The grain size distribution diagram of the aluminum-silicon alloy prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0020] Figure 2 Graph showing the tensile stress-strain curves of the aluminum silicon alloys prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0021] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, the solutions and specific embodiments are described in detail below.

[0022] An embodiment of the present application provides an aluminum-silicon alloy, which includes the following components, measured by mass percentage: 8.5% to 10% Si; 0.1% to 0.5% Mg; 0.35% to 0.65% Mn; 0.1% to 0.2% Fe; 0.05% to 0.2% Nb; 0.01% to 0.04% B; 0.01% to 0.02% Sr, 0.5% to 1% TiCN; the total content of other impurities is ≤0.5%, and the balance is Al.

[0023] It can be understood that in the aluminum silicon alloy, by mass percentage, Si includes but is not limited to 8.5%, 8.7%, 8.85%, 9%, 9.1%, 9.3%, 9.45%, 9.6%, 9.8%, 10%; Mg includes but is not limited to 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.48%, 0.5%; Mn includes but is not limited to 0.35%, 0.4%, 0.45%, 0.5%, 0.56%, 0.6%, 0.65%; Fe includes But not limited to 0.1%, 0.12%, 0.14%, 0.15%, 0.17%, 0.19%, 0.2%; Nb includes but is not limited to 0.05%, 0.1%, 0.13%, 0.15%, 0.18%, 0.2%; B includes but is not limited to 0.01%, 0.02%, 0.03%, 0.04%; Sr includes but is not limited to 0.01%, 0.013%, 0.015%, 0.018%, 0.02%; TiCN includes but is not limited to 0.5%, 0.55%, 0.6%, 0.65%, 0.68%, 0.72%, 0.8%, 0.85%, 0.9%, 1%; in some examples, it can be within the range formed by any two of these point values ​​as end values, the same below.

[0024] In the aluminum-silicon alloy of the present invention, Si element is an alloy basic element, and the addition of Si can reduce volume shrinkage and improve fluidity, thereby improving the castability of the aluminum alloy; at the same time, the addition of Si will lead to the formation of large-layer lamellar eutectic Si, and the large-piece lamellar eutectic Si structure can be transformed into fine fibers through a trace amount of Sr modification treatment to improve the plasticity of the alloy; Mg element and Si element can form Mg2Si phase, and after aging heat treatment, a dispersion strengthening phase can be precipitated in the alloy to improve the strength of the alloy; Mn element can transform the lamellar β-Fe phase in the alloy into a rounded Chinese character-shaped α-Fe phase, thereby improving the ductility of the alloy, and at the same time, the addition of Mn element will reduce the solubility of Fe element in Al, improve demoulding property, thereby extending the life of the mold; the role of Nb element and B element is to improve the nucleation efficiency of the substrate by forming nucleation substrates NbB2 and AlNB3 that are resistant to "Si" poisoning; the role of TiCN is to densely adhere to the periphery of the grains, greatly restricting the rapid growth of the grains, and Nb-B and TiCN have a great influence on the nucleation efficiency of the substrate. The composite addition of CN eventually forms a spatial distribution of Nb-BT i CN particles with a "core-shell" structure in the core and boundary of the grains, while having the advantages of micron-scale particles providing nucleation substrate and nano-scale particles restricting growth, and has a higher refinement efficiency than conventional refiners.

[0025] It can be understood that in the aluminum-silicon alloy provided in the present application, the mutual cooperation and restriction between the components can achieve higher refinement requirements of the aluminum-silicon alloy, and it has better tensile strength, yield strength and plasticity, which are not brought by the components alone.

[0026] In some of the embodiments, the mass ratio of Mn to Fe is (1.5-3.2):1, and the mass ratio of Nb to B is (5-9):1.

[0027] It can be understood that the mass ratio of Mn and Fe includes but is not limited to 1.5:1, 2:1, 2.2:1, 2.3:1, 2.5:1, 2.7:1, 2.9:1, 3:1, 3.2:1; the mass ratio of Nb and B includes but is not limited to 5:1, 6:1, 6.5:1, 7:1, 8:1, 8.5:1, 9:1.

[0028] In some of the embodiments, Nb and B are added in the form of Al-Nb-B master alloy.

[0029] In some of the embodiments, the TiCN is a ceramic particle with a size of 20 to 200 nanometers.

[0030] The present invention also provides a method for preparing the aluminum-silicon alloy, comprising the following steps:

[0031] S1. Batching and smelting: Si, Mn and Al are batched according to mass percentage and put into a smelting furnace. The temperature of the smelting furnace is raised to 790°C-810°C until all the above alloys are melted; the temperature of the smelting furnace is lowered to 775°C-785°C, Nb and B are added to the melt, and stirred for 30s-40s after Nb and B are completely melted; the temperature of the smelting furnace is further lowered to 730°C-735°C, and Mg and Sr are added; Fe is added to the melt along with Al as an impurity of Al, and its mass percentage is controlled at 0.1%-0.2%.

[0032] S2. Refining and pouring: After degassing and refining for 30min to 35min, remove the slag; after removing the slag, add TiCN into the melt and stir for 3min to 5min, and then ultrasonically treat for 3min to 5min; after refining, let it stand for 15min to 20min, and then pour it, and the pouring temperature is 730℃ to 740℃.

[0033] In some of the embodiments, in step S1, the selected elements are added in the form of: Al-Si master alloy, Al-Mn master alloy, Al-Sr master alloy, industrial pure aluminum with a purity of 99.9%, Al-Nb-B master alloy, and industrial pure magnesium with a purity of 99.9%.

[0034] In some implementations, in step S2, the refining gas used is argon gas, and the gas flow rate is 9 L / min to 11 L / min.

[0035] In some of the embodiments, in step S2, after adding TiCN into the melt, the melt is stirred thoroughly for 3 minutes using a graphite rod.

[0036] In some embodiments, in step S2, the ultrasonic vibration frequency is 19KHz to 21KHz, and during operation, the ultrasonic probe is inserted under the liquid surface, and the probe is 10mm to 15mm away from the liquid surface.

[0037] The present invention also provides an application of the aluminum-silicon alloy in automobile structural parts.

[0038] The present invention also provides an aluminum-silicon alloy product as mentioned above, comprising the aluminum-silicon alloy as mentioned above.

[0039] The above aluminum-silicon alloy is used to prepare aluminum-silicon alloy products, which can greatly improve the strength of the aluminum-silicon alloy products, especially the yield strength, and at the same time improve the tensile strength and elongation of the alloy products.

[0040] In some of the examples, aluminum-silicon alloy products include but are not limited to automotive structural parts, wires and cables, rail profiles, and electrodes.

[0041] In some examples, the material of the aluminum-silicon alloy product may be the aluminum-silicon alloy mentioned above, that is, the aluminum-silicon alloy product is directly prepared by using the aluminum-silicon alloy mentioned above. In other examples, the material of the aluminum-silicon alloy product may include other materials in addition to the aluminum-silicon alloy mentioned above.

[0042] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0043] Embodiment 1:

[0044] This embodiment comprises the following components by mass percentage:

[0045] 8.5% Si; 0.23% Mg; 0.55% Mn; 0.2% Fe; 0.08% Nb; 0.01% B; 0.012% Sr; 0.5% TiCN; the content of other uncontrollable impurity elements is controlled at ≤0.5%, and the balance is Al.

[0046] In this embodiment, the alloy is prepared according to the following steps:

[0047] Material preparation: according to the proportion of alloy components, Si, Mn, Nb, B, Mg, Al, TiCN and other elements are added in the form of Al-Si master alloy, Al-Mn master alloy, Al-Sr master alloy, Al-Nb-B master alloy, 99.9% industrial pure magnesium, 99.9% industrial pure aluminum and TiCN nano-ceramic particles.

[0048] Melting: Put AlSi master alloy, Al-Mn master alloy and 99.9% pure industrial aluminum into a resistance melting furnace, raise the temperature to 790℃~810℃ until the alloy is completely melted; then cool down to 775℃~785℃, add Al-Nb-B master alloy, stir for 30s~40s after it is completely melted; further reduce the melting furnace temperature to 730℃~735℃, then add 99.9% pure industrial magnesium and Al-Sr master alloy. In order to prevent oxidation and burning, the magnesium ingot is wrapped with aluminum foil and pressed into the aluminum melt with a graphite bell.

[0049] Refining: Degassing and refining are carried out with argon gas, and the gas flow rate is 9L / min~11L / min. Degassing is carried out after 30~35min. After deslagging, the TiCN ceramic particles wrapped in aluminum foil are pressed into the aluminum melt with a graphite bell jar, and fully stirred for 3min, and ultrasonic vibration is carried out for 3~5min. The ultrasonic vibration frequency is 19~21KHz, and the ultrasonic probe is inserted 10~15mm below the liquid surface during operation; after ultrasonic vibration, it is allowed to stand for 15~20min.

[0050] Pouring: The hydrogen content of the melt is measured by a hydrogen meter, and the pinhole degree is not greater than Level 1 specified in GB / T7946.3 Pinhole Degree of Cast Aluminum Alloy. After the test is qualified, pouring is carried out, and the pouring temperature is controlled at 730℃~740℃.

[0051] Squeeze casting: The aluminum liquid is transferred to the extrusion casting machine. The extrusion equipment used is SCH-550 indirect extrusion casting machine, the extrusion pressure is 150Mpa, and the extrusion speed is 110mm / s.

[0052] Embodiment 2:

[0053] This embodiment comprises the following components by mass percentage:

[0054] 9% Si; 0.18% Mg; 0.5% Mn; 0.15% Fe; 0.1% Nb; 0.03% B; 0.015% Sr; 0.6% TiCN, the content of other uncontrollable impurity elements is also controlled at ≤0.5%, and the balance is Al.

[0055] The preparation method of the aluminum-silicon alloy in this embodiment 2 is the same as that in embodiment 1.

[0056] Comparative Example 1:

[0057] In this comparative example, only Al-Ti-B refiner is added, and nano-sized TiCN ceramic particles and Al-Nb-B refiner are not added. The mass percentages of the components of the hypoeutectic Al-Si alloy are: 8.5% Si; 0.24% Mg; 0.56% Mn; 0.19% Fe; 0.1% Ti; 0.02% B; 0.012% Sr.

[0058] In this comparative example, the alloy was prepared according to the following steps:

[0059] Material preparation: According to the proportion of alloy components, Si, Mn, Ti, B, Mg, Al and other elements are added in the form of Al-Si master alloy, Al-Mn master alloy, Al-Sr master alloy, Al-T iB master alloy, 99.9% industrial pure magnesium and 99.9% industrial pure aluminum respectively.

[0060] Melting: Put Al-Si master alloy, Al-Mn master alloy and 99.9% pure industrial aluminum into a resistance melting furnace, raise the temperature to 790℃~810℃ until the alloy is completely melted; then cool down to 775℃~785℃, add Al-TiB master alloy, stir for 30s~40s after it is completely melted; further reduce the melting furnace temperature to 730℃~735℃, then add 99.9% pure industrial magnesium and Al-Sr master alloy. In order to prevent oxidation and burning, the magnesium ingot is wrapped with aluminum foil and pressed into the aluminum melt with a graphite bell.

[0061] Refining: Use argon gas for degassing refining, the gas flow rate is 9L / min~11L / min, and slag is removed after 30~35min of degassing; let it stand for 15~20min after slag removal.

[0062] Pouring: The hydrogen content of the melt is measured by a hydrogen meter, and the pinhole degree is not greater than Level 1 specified in GB / T7946.3 Pinhole Degree of Cast Aluminum Alloy. After the test is qualified, pouring is carried out, and the pouring temperature is controlled at 730℃~740℃.

[0063] Squeeze casting: The aluminum liquid is transferred to the extrusion casting machine. The extrusion equipment used is SCH-550 indirect extrusion casting machine, the extrusion pressure is 150Mpa, and the extrusion speed is 110mm / s.

[0064] Comparative Example 2:

[0065] In this comparative example, only Al-Nb-B refiner is added, and nano-sized TiCN ceramic particles are not added. The mass percentages of the components of the hypoeutectic Al-Si alloy are: 8.6% Si; 0.22% Mg; 0.56% Mn; 0.2% Fe; 0.15% Nb; 0.018% B; 0.010% Sr.

[0066] In this comparative example, the alloy was prepared according to the following steps:

[0067] Material preparation: According to the proportion of alloy components, Si, Mn, Nb, B, Mg, Al and other elements are added in the form of AlSi master alloy, Al-Mn master alloy, Al-Sr master alloy, Al-Nb-B master alloy, 99.9% industrial pure magnesium and 99.9% industrial pure aluminum respectively.

[0068] Melting: Put AlSi master alloy, Al-Mn master alloy and 99.9% pure industrial aluminum into a resistance melting furnace, raise the temperature to 790℃~810℃ until the alloy is completely melted; then cool down to 775℃~785℃, add Al-Nb-B master alloy, stir for 30s~40s after it is completely melted; further reduce the melting furnace temperature to 730℃~735℃, then add 99.9% pure industrial magnesium and Al-Sr master alloy. In order to prevent oxidation and burning, the magnesium ingot is wrapped with aluminum foil and pressed into the aluminum melt with a graphite bell.

[0069] Refining: Use argon gas for degassing refining, the gas flow rate is 9L / min~11L / min, and slag is removed after 30~35min of degassing; let it stand for 15~20min after slag removal.

[0070] Pouring: The hydrogen content of the melt is measured by a hydrogen meter, and the pinhole degree is not greater than Level 1 specified in GB / T7946.3 Pinhole Degree of Cast Aluminum Alloy. After the test is qualified, pouring is carried out, and the pouring temperature is controlled at 730℃~740℃.

[0071] Squeeze casting: The aluminum liquid is transferred to the extrusion casting machine. The extrusion equipment used is SCH-550 indirect extrusion casting machine, the extrusion pressure is 150Mpa, and the extrusion speed is 110mm / s.

[0072] The castings obtained in Example 1 and Comparative Examples 1 and 2 were characterized for grain size. In order to observe the grain size more clearly, Barker's solution was used for anodic coating treatment, and then metallographic photographs were obtained under the polarized light mode of an optical microscope. The grain size distribution of Example 1 is shown in the attached figure. Figure 1 As shown, it can be seen that the alloy with composite addition of Al-Nb-B and TiCN has smaller sizes at the edge, 1 / 2 radius and core area of ​​the sample, which proves that the trace elements added in the present invention play an important role in refining the structure.

[0073] The castings obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to room temperature tensile performance tests. The tensile curves are shown in the attached figure. Figure 2 The specific test data is shown in Table 1.

[0074] By comparing Examples 1 and 2 with Comparative Examples 1 and 2, when Al-Nb-B is added alone, the strength of the alloy, especially the yield strength, can be greatly improved, and when Al-Nb-B and TiCN are added in combination, the tensile strength and elongation of the alloy can be improved at the same time. By comparison, it can be shown that Nb, B and TiCN in the present invention can have an important influence on the microstructure and properties of the alloy.

[0075] The above contents are only embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation disclosed in the present invention specification, or any behavior directly or indirectly applied to other related technical fields, shall be deemed to fall within the patent protection scope of the present invention.

[0076] Table 1 Room temperature tensile mechanical properties of castings obtained in various embodiments and comparative examples

[0077]

Claims

1. An aluminum-silicon alloy, characterized in that: Calculated by mass percentage, it includes the following components: 8.5% to 10% Si; 0.1% to 0.5% Mg; 0.35% to 0.65% Mn; 0.1% to 0.2% Fe; 0.05% to 0.2% Nb; 0.01% to 0.04% B; 0.01% to 0.02% Sr, 0.5% to 1% TiCN; the total content of other impurities is ≤0.5%, and the balance is Al.

2. The aluminum-silicon alloy according to claim 1, characterized in that: The mass ratio of the Mn to the Fe is (1.5-3.2):1, and the mass ratio of the Nb to the B is (5-9):

1.

3. The aluminum-silicon alloy according to claim 1, characterized in that: The Nb and the B are added in the form of an Al-Nb-B master alloy.

4. The aluminum-silicon alloy according to any one of claims 1 to 3, characterized in that: The TiCN is a ceramic particle with a size of 20 to 200 nanometers.

5. A method for preparing an aluminum-silicon alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Batching and smelting: Si, Mn and Al are batched according to mass percentage and put into a smelting furnace. The temperature of the smelting furnace is raised to 790°C to 810°C until all the above alloys are melted. The temperature of the smelting furnace is lowered to 775°C to 785°C, Nb and B are added to the melt, and stirred for 30s to 40s after Nb and B are completely melted. The temperature of the smelting furnace is further lowered to 730°C to 735°C, and then Mg and Sr are added. S2. Refining and pouring: After degassing and refining for 30min to 35min, remove the slag; after removing the slag, add TiCN into the melt and stir for 3min to 5min, and then ultrasonically treat for 3min to 5min; after refining, let it stand for 15min to 20min, and then pour it, and the pouring temperature is 730℃ to 740℃.

6. The method for preparing aluminum-silicon alloy according to claim 5, characterized in that: In step S1, the selected elements are added in the form of: Al-Si master alloy, Al-Mn master alloy, Al-Sr master alloy, industrial pure aluminum with a purity of 99.9%, Al-Nb-B master alloy, and industrial pure magnesium with a purity of 99.9%.

7. The method for preparing aluminum-silicon alloy according to claim 5, characterized in that: In step S2, after TiCN is added into the melt, a graphite rod is used to stir the melt for 3 minutes.

8. The method for preparing an aluminum-silicon alloy according to any one of claims 5 to 7, characterized in that: In step S2, the ultrasonic vibration frequency is 19KHz to 21KHz, and during operation, the ultrasonic probe is inserted under the liquid surface, and the probe is 10mm to 15mm away from the liquid surface.

9. Use of the aluminum-silicon alloy according to any one of claims 1 to 4 in the preparation of automotive structural parts.

10. An aluminum-silicon alloy product, characterized in that: Comprising the aluminum-silicon alloy as described in any one of claims 1 to 4.